Association between thermal comfort and work-related symptoms in low energy level office(LEO) buildings, Putrajaya. - Shaharon, Mohd Nafiz; Jalaludin, Juliana (Malaysian Public Health Specialist Association, 2011)
The issues of workers comfort and workspace quality in office buildings have gained animportant concerned from the Ministry of Energy, Water and Green Technology, Malaysia. Newenergy efficient building concepts and technologies require a revision of comfort standards, tocreate suitable thermal condition in avoiding occupants’ dissatisfaction, adverse effect on theirproductivity and overall building performance. A quantitative assessment was conducted in aLow Energy Office (LEO) building, in Putrajaya using Babuc-A (Portable air quality monitor)and a qualitative assessment using set of questionnaire adapted from ASHRAE Standard (2004)and IEQ survey questionnaire. Total of 99 respondents were chosen using a stratified randomsampling and based on the worker preferences the results showed that sinusitis ( x2=7.50,p<0.05), eczema ( x2=8.60, p<0.05) and fatigue ( x2=10.24, p<0.05) was reported for the last fourweeks and stuffy nose ( x2=8.59, p<0.05) was a current reported symptoms on the studied day.However, statistical study showed no significant association between work-related symptomsand PMV for LEO building suggesting that the current thermal environment did not causing thework-related symptoms in the office. The thermal comfort zone for this building was in thetemperature range of 21.6oC to 23.6oC and relative humidity of between 42 to 54 percent. Theresults suggested the thermal condition was in the acceptable range of ISO 7730 (calculation of PMV and PPD) and that a lower room temperature was preferred by Malaysian in officeenvironment compared with the temperature criteria cited in ASHRAE Standard-55